676 Impact of transcatheter aortic valve implantation in patients with severe aortic stenosis and concomitant mitral regurgitation. (8th December 2021) - Manzi, Lina; Ilardi, Federica; Simonetti, Fiorenzo; Verde, Nicola; Franzone, Anna; Angellotti, Domenico; Avvedimento, Marisa; Leone, Attilio; Castiello, Domenico; Manzo, Rachele; Mariani, Andrea; Piccolo, Raffaele; et al.
Abstract: Aims: Severe aortic stenosis (AS) and functional mitral regurgitation (MR) frequently coexist. There is no consensus about the optimal therapeutic strategy for patients with combined valve disease. Evidence has shown that double valve surgery is associated with high complication rates and mortality, whereas MR severity may improve after transcatheter aortic valve implantation (TAVI). To date, little is known on prognostic parameters associated with MR improvement after TAVI. Recently, a new echocardiographic parameter based on the ratio between peak E velocity and peak atrial longitudinal strain (E/PALS) has demonstrated to be accurate and sensitive in the prediction of elevated filling pressure. Its role in the setting of AS patients undergoing TAVI has never been investigated. Our study aims to evaluate haemodynamic conditions and left ventricular (LV) systolic and diastolic function in patients with severe AS and concomitant MR undergoing TAVI and to identify new echocardiographic parameters associated with MR improvement 1 month after the aortic valve replacement. Methods: We prospectively enrolled 87 consecutive patients (mean age 80 ± 6 years) with severe symptomatic AS and concomitant MR undergoing TAVI between 2016 and 2021, for whom a complete echocardiographic assessment was available at baseline and 1 month after the procedure, selected from the EffecTAVI registry. Exclusion criteria were prior valve surgery, severe mitral stenosis, permanent atrial fibrillation, and poor ultrasound acoustic window. Echo-Doppler assessment, including global longitudinal strain (GLS) and peak atrial longitudinal strain (PALS), was performed before and after 1 month to TAVI procedure. Changes (Δ) of the main echo parameters before and after intervention were computed. Results: A month after the procedure, 20 (23%) patients had a reduction of at least one degree of MR ( P <0.001). Dividing study population in two groups, based on whether or not MR was reduced after TAVI, we found that patients with MR improvement had higher LV end-diastolic volume ( P = 0.036) and left atrial volume ( P = 0.015) at baseline compared with those without MR reduction. After TAVI no significant differences were found in heart chambers size between the two groups, but a significant increase in PALS (23.2 ± 7.3 vs. 22.3 ± 7, P =0.028), together with a reduction in E/A ratio (0.69 ± 0.14 vs. 0.90 ± 0.46, P = 0.046) were detected in patients with MR reduction. Furthermore, Δ E/PALS (−17.3±34.4% vs. 3.9±35.0% P =0.027), Δ E/A (−12.6±33.9% vs. 24.7±64.3%, P =0.018) and Δ systolic pulmonary artery pressure (sPAP) (−13.0±20.2% vs. −2.0±18.3, P =0.031) were significantly higher in patients with MR improvement to compared those without MR reduction. By the multivariate logistic regression analysis performed in the pooled population, Δ E/PALS (OR 0.968, 95% CI: 0.947–0.990, P =0.005), together with LV mass at baseline (OR 1.056, 95% CI: 1.007–1.107, P = 0.024) appeared to be independently associated with MR reduction post-TAVI. Conclusions: Our study demonstrated that: after TAVI in a significant percentage of patients a relevant improvement in concomitant MR was detected; in the group of patients with improved MR a parallel improvement of sPAP, E/A and E/PALS ratio post TAVI was found; Δ E/PALS appears to be the main parameter independently associated with the reduction of MR severity.